Analisis Kesediaan Berbagi Identitas Digital berdasarkan PMT: Perceived Severity, Perceived Vulnerability, Response Efficacy, dan Usia - Muhammad Arya Dwi Septianto; Diah Priharsari; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The many features provided by social media can make it easy for users to share personal information. The lack of a sense of concern and understanding of privacy in society can have negative consequences. This is caused by the different behavior of each individual, so that each individual will have different intentions and interests in the willingness to share privacy, especially identity. The purpose of this study is to find out how the willingness to share digital identity on social media is based on Protection Motivation Theory, especially the factors of Perceived Severity (PS), Perceived Vulnerability (PV), and Response Efficacy (RE) which influence Concern for Information Privacy (KIP). This study also aims to determine differences in user behavior in sharing their identities on social media based on Age (AG). From the results of the research conducted, no differences in behavior were found based on the user's age range on the willingness to share digital identities (KBI), but concerns about privacy information have an influence on the willingness to share digital identities. Perceived Severity and Perceived Vulnerability also affect the sense of concern about Privacy Information. But Response Efficacy has no influence on the sense of Privacy Information Concern.